Investigating the onset of insulin resistance and non-alcoholic fatty liver disease in obesity-induced cardiac dysfunction - Boshoff, Anel W. (Stellenbosch : Stellenbosch University, 2019)
Thesis (MMed)--Stellenbosch University, 2019.